High treatment success rate for multidrug-resistant and extensively drug-resistant tuberculosis using a bedaquiline-containing treatment regimen - Ndjeka, Norbert; Schnippel, Kathryn; Master, Iqbal; Meintjes, Graeme; Maartens, Gary; Romero, Rodolfo; Padanilam, Xavier; Enwerem, Martin; Chotoo, Sunitha; Singh, Nalini; Hughes, Jennifer; Variava, Ebrahim; et al. (The European respiratory journal, 2018)
South African patients with rifampicin-resistant tuberculosis (TB) and resistance to fluoroquinolones and/or injectable drugs (extensively drug-resistant (XDR) and preXDR-TB) were granted access to bedaquiline through a clinical access programme with strict inclusion and exclusion criteria.PreXDR-TB and XDR-TB patients were treated with 24 weeks of bedaquiline within an optimised, individualised background regimen that could include levofloxacin, linezolid and clofazimine as needed. 200 patients were enrolled: 87 (43.9%) had XDR-TB, 99 (49.3%) were female and the median age was 34 years (interquartile range (IQR) 27-42). 134 (67.0%) were living with HIV; the median CD4 count was 281 cells·μL (IQR 130-467) and all were on antiretroviral therapy.16 out of 200 patients (8.0%) did not complete 6 months of bedaquiline: eight were lost to follow-up, six died, one stopped owing to side effects and one was diagnosed with drug-sensitive TB. 146 out of 200 patients (73.0%) had favourable outcomes: 139 (69.5%) were cured and seven (3.5%) completed treatment. 25 patients (12.5%) died, 20 (10.0%) were lost from treatment and nine (4.5%) had treatment failure. 22 adverse events were attributed to bedaquiline, including a QT interval corrected using the Fridericia formula (QTcF) >500 ms (n=5), QTcF increase >50 ms from baseline (n=11) and paroxysmal atrial flutter (n=1).Bedaquiline added to an optimised background regimen was associated with a high rate of successful treatment outcomes for this preXDR-TB and XDR-TB cohort.